Poor Housing Construction Associated with Increased Malaria Incidence in a Cohort of Young Ugandan Children - Snyman, Katherine; Mwangwa, Florence; Bigira, Victor; Kapisi, James; Tamara, D. Clark; Sturrock, Hugh; Gosling, Roly; Dorsey, Grant (The American journal of tropical medicine and hygiene, 2015)
Despite the use of accepted interventions to combat malaria, such as insecticide-treated bed nets and artemisinin-based combination therapy, malaria remains a leading cause of morbidity and mortality in Uganda. We investigated associations between household factors and malaria incidence in a cohort of children living in a highly endemic region of Uganda. Living in a modern house, defined as the use of non-earth floors, non-thatched roofs, and non-mud walls, was associated with approximately half malaria incidence compared with living in a traditional home (incidence rate ratio [IRR] = 0.54, P = 0.001). Other factors found to be associated with a lower incidence of malaria included living in town versus rural setting; sleeping in a room with openings to the outside (windows, eaves, and airbricks); and having an older and more educated primary caregiver. This study adds to the growing body of evidence that improved house construction may be associated with a lower risk of malaria.